Towards a post-extractivist and comunalist paradigm of territorial development for Latin America - Ramírez-Miranda, César Adrián (2024)
The objective of this contribution is to provide elements for the construction of a new Latin American paradigm of territorial development based on the extensive experience available in the region as well as on the recognition of the diversity that characterizes its territories. A reflection situated on two fronts is presented: historically in the political conjuncture that Latin America is experiencing and spatially in the southern portion of the Isthmus of Tehuantepec, Oaxaca, Mexico. The argument includes a characterization of the elements that underline the need to give centrality to the food issue and the rural space in the perspective of territorial development, a brief recapitulation on the institutional aspect of the territorial approach to development, a synthesis of the elements that contribute to the construction of a new Latin American paradigm of territorial development and the reflection on the experience of the Autonomous Communal University of Oaxaca, referring especially to its actions in the Isthmus of Tehuantepec. The main result of this reflection is to highlight the challenges facing the implementation of a paradigm of transformative popular science. It is concluded that the reconstitution of community relations is a central task to shape popular-based territorial development proposals.